Halal Standards and Regulations: Implications for Producers and Consumers in Literature Studies - Jailani, Novalini (Darul Yasin Al Sys, 2024)
This study aims to analyze in depth halal standards and regulations and their implications for producers and consumers. In addition, this study aims to identify and understand the challenges faced by producers in complying with halal standards, as well as their impact on consumer purchasing decisions. This research was carried out using the library research method, using a qualitative approach. The data sources used are secondary data sources, namely collecting and then understanding, and analyzing previous articles, news, and books with relevant topics, be it journal articles or online media, as well as books that discuss halal standards and regulations. The data collection techniques used in this study are literature and documentation. Meanwhile, the data analysis technique applied in this study is a descriptive method. In this study, the limitations of the review are first, the articles or journals used are those published in 2016-2024. The results of the study show that the implementation of halal standards has been proven to have a positive influence on the producers company's internal operations, although then, at the same time they as producers face complex challenges such as the heterogeneity of halal standards, questionable raw materials, unethical practices, communication gaps, acceptance variability, human resource management issues, supply chain bottlenecks, and improper Islamic marketing orientation. For consumers, halal standards play an important role in shaping purchasing decisions, especially in the Muslim community. Consumer awareness of halal regulations is not only about recognizing the halal logo or understanding the basic principles of halal. This involves a deeper understanding of the entire halal certification process, the authorities involved, and its implications for product quality and safety.